Gastos pre-operativos: su tratamiento en el impuesto a la renta - Mur Valdivia, Miguel (2013)
Mary and Peter fund a company dedicated tomaking clothes. They, therefore, must provide enough capital to sustain their business. After ten years they decide to expand and for this reason they make more disbursements. Do all disbursements constitute pre-operating expenses? Can they be deducted? Which tax treatment should this company receive? In this essay, the author seeks not only to define what a pre-operating expense is, but healso says what the requirements for them to be deducted are. In his explanation, with the support of diverse jurisprudence, he refers to the some key issues such as the expansion of the activity and the role of Tax Administration that serve to evaluate the specific cases of scientific and technological expenses.